Comparison of techniques for the measurement of skin temperature during exercise in a hot, humid environment - McFarlin, Brian K; Venable, Adam S; Williams, Randall R; Jackson, Allen W (Biology of Sport, 2015)
Exercising or working in a hot, humid environment can results in the onset of heat-related illness when an individual’s temperature is not carefully monitored. The purpose of the present study was to compare three techniques (data loggers, thermal imaging, and wired electrodes) for the measurement of peripheral (bicep) and central (abdominal) skin temperature. Young men and women (N=30) were recruited to complete the present study. The three skin temperature measurements were made at 0 and every 10-min during 40-min (60% VO 2 max) of cycling in a hot (39±2°C), humid (45±5% RH) environment. Data was statistically analyzed using the Bland-Altman method and correlation analysis. For abdominal skin temperature, the Bland-Altman limits of agreement indicated that data loggers (1.5) were a better index of wired than was thermal imaging (3.5), For the bicep skin temperature the limits of agreement was similar between data loggers (1.9) and thermal (1.9), suggesting the both were suitable measurements. We also found that when skin temperature exceeded 35ºC, we observed progressively better prediction between data loggers, thermal imaging, and wired skin sensors. This report describes the potential for the use of data loggers and thermal imaging to be used as alternative measures of skin temperature in exercising, human subjects